SETTING JARINGAN MIKROTIK DAN PEMBUATAN CHANNEL YOUTUBE UNTUK MASJID JAMI’ MANARUL HUDA SUMBERSARI KOTA MALANG - As'ad, Mohamad; Firdaus, Nasrul; Syaifullah, Ali (UNIVERSITAS PGRI MADIUN, 2021)
Abstract. Information technology is one of the tools in various fields, including in the field of Islamic da'wah. Islamic da'wah with information technology in the form of live streaming recitation to youtube (online da'wah) is viral now. This online da'wah was the wish of Takmir and the congregation of Masjid Jami' Manarul Huda. Setting up the internet network with Mikrotik and making channels on youtube at the Masjid Jami' Manarul Huda was community empowerment, namely the application of science and technology to the community at the Masjid Jami' Manarul Huda. This program was a form of community service from STMIK PPKIA Pradnya Paramita (STIMATA) Malang. This community service aims to apply the knowledge that was on campus to the wider community, especially the Masjid Jami 'Manarul Huda so that they can carry out wider preaching and serve the congregation. The installation of the Telkom Indihome network was carried out at the end of December 2018 and also proxy settings and the creation of a youtube channel, namely